Bussines Relationship Management Plan on Development and Aplication of Information Technology using ITIL v3 - Ramadhan, Rizki; Amelia, Tan; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Development and Application of Information Technology (PPTI) is part of Institute Business and Informatics Stikom Surabaya. PPTI’s Main Function is to support visions, missions, and goals. To achieving the visions, missions, and goals, PPTI must have a good plan, including the mechanism plan to manage the relations between PPTI it self and with the service user. The Mechanism process will be used by PPTI to fulfill the Stikom Surabaya Information Technology’s needs. to achiveing the goals, PPTI need to do some research that based on Information Technology Infrastructur Library v3 (ITIL v3) standart, which is Service Strategy. Process of making the document refered from Service Strategy process number 5, Business Relationship Management. The result of this research is service portfolio document which contain customer portfolio, socialization’s standart and procedure, training’s standart and procedure, user complaint’s standart and procedure, socialization’s policy, training’s policy, and user’s complaint policy, that will be used by PPTI later.